Modeling the Impacts of Boreal Deforestation on the Near-Surface Temperature in European Russia - Zhihui Li; Xiangzheng Deng; Qingling Shi; Xinli Ke; Yingcheng Liu (Advances in Meteorology)
Boreal deforestation plays an important role in affecting regional and global climate. In this study, the regional temperature variation induced by future boreal deforestation in European Russia boreal forest region was simulated based on future land cover change and the Weather Research and Forecasting (WRF) model. This study firstly tested and validated the simulation results of the WRF model. Then the land cover datasets in different years (2000 as baseline year, 2010, and 2100) was used in the WRF model to explore the impacts of boreal deforestation on the near-surface temperature. The results indicated that the WRF model has good ability to simulate the temperature change in European Russia. The land cover change in European Russia boreal forest region, which will be characterized by the conversion from boreal forests to croplands (boreal deforestation) in the future 100 years, will lead to significant change of the near-surface temperature. The regional annual temperature will decrease by 0.58°C in the future 100 years, resulting in cooling effects to some extent and making the near-surface temperature decrease in most seasons except the spring.